Diagnosis on defect caused by humidity in a university's accommodation: a literature study / Zaimah Zainal Abidin, Nur Azfahani Ahmad and Alia Abdullah Salleh - Zainal Abidin, Zaimah; Ahmad, Nur Azfahani; Abdullah Salleh, Alia (2018)
In Malaysia, buildings are developed strictly according to the Malaysian Standard and the British Standard. However, due to improper maintenance performance, building issues have increased rapidly creating a concern among building users. Building issues such as defects are predominantly raised due to climatic characteristics, for instance, extreme weather, high heat and increased humidity exposure. Due to such issues, buildings are exposed to Building-Related Illness (BRI) which may affect the building users. The aim for this paper is to perform a preliminary work related to the diagnosis work for defect on humidity in university’s accommodation in order to allow a proper remedial work towards a more sustainable university. The objectives are to identify the common defect related to humidity found at university accommodation, to diagnoses level of defect related to humidity found at university accommodation and to determine the suitable diagnosis for humidity’s defect at the students’ accommodation in university. University accommodations in Malaysia are chosen as the subject of research since these accommodations always have to face this issue. If humidity defects in students’ accommodation are not treated accordingly, issues may arise on the numbers of occurrence for BRI for these accommodations.